Christian brethren churches in Papua New Guinea, 1951-1995 how did it all happen? - Thorp, Dennis; Thorp, Barbara (Auckland, NZ Dennis and Barbara Thorp, 1996)
Includes bibliographical references.
Donated by the authors. A research requirement for the Master of Arts in Ministry course, Moody Bible Institute, Chicago, IL, USA.
Keywords: Brethren movement -- history -- Papua New Guinea